1979
DOI: 10.1111/j.1440-6055.1979.tb00817.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biology and Laboratory Rearing of a New Leptopiine Weevil, a Pest of Legumes in Queensland

Abstract: The temporal incidence of the various life history stages of a new leptopiine weevil (Coleoptera: Curculionidae) is given. Distribution records were all from far north coastal Queensland. Most adults emerged from earthen cells (at a mean depth of 100 mm) with the first storm rains yielding approximately 50 mm in October-November.Adult pairs of the leptopiine were fed on germinated Vigna sinensis seed and provided with 25 mm squares of tissue paper as oviposition substrate. Eggs were incubated at temperatures r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
0
11
0
1
Order By: Relevance
“…The latter attack pasture legumes but have not become established on agricultural land near Tolga. Larvae of a leptopine weevil studied by Elder et al (1979) pupate from August onwards and by late September adults are present in the soil. They emerge immediately after the first isolated heavy storms, which may occur as early as October.…”
Section: High Soil Temperatures and Pupationmentioning
confidence: 99%
“…The latter attack pasture legumes but have not become established on agricultural land near Tolga. Larvae of a leptopine weevil studied by Elder et al (1979) pupate from August onwards and by late September adults are present in the soil. They emerge immediately after the first isolated heavy storms, which may occur as early as October.…”
Section: High Soil Temperatures and Pupationmentioning
confidence: 99%
“…Early in the development of outbreaks, swarms have been recorded in the Gulf, Gulf Rivers and/or Barkly Tableland within or near regions of cracking clay soils (Fig. 1) (Key 1938;Bullen 1969;Elder et al 1979;Elder 1997;Australian Plague Locust Commission, unpubl. records, 1987-1998.…”
Section: Introductionmentioning
confidence: 99%
“…The spur-throated locust, Austracris guttulosa (Walker) (formerly Nomadacris guttulosa [Walker] [ Key & Rentz 1994]), has long been recognised as an occasional serious pest of crops in Australia's north (Weddell 1937;Key 1938;Bullen 1969;Elder et al 1979) and temperate south-east (Casimir & Edge 1979). Bullen (1969) found that five of the seven outbreaks between 1935 and 1968 began in years of average or above average rainfall following drought.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, las crías sobre dietas artificiales y semiartificiales no han resultado exitosas (Zenner, 1990). Por otra parte, los sistemas de cría en laboratorio desarrollados para otras especies de la subfamilia Entiminae a la que pertenece P. vorax no se adecuan a los hábitos y requerimientos ecológicos del gusano blanco (Elder et al, 1979;Shimoji y Yamagishi, 2002;Fisher, 2006).…”
unclassified